UV-A and FR irradiation improves growth and nutritional properties of lettuce grown in an artificial light plant factory - He, Rui; Zhang, Yiting; Song, Shiwei; Su, Wei; Hao, Yanwei; Liu, Houcheng (Food chemistry, 2021)
•Ultraviolet A (UV-A) supplementation reduced the leaf area and biomass in lettuce.•UV-A supplementation improved the chlorophyll, soluble protein, soluble sugar, vitamin C contents.•UV-A supplementation improved the flavonoid, polyphenol, and anthocyanin contents and DPPH free radical-scavenging rate.•Far-red (FR) light yielded larger leaf area, but no significant improvement in biomass.•Combined UV-A and FR light improved leaf area and biomass, but reduced phytochemical contents. This study investigated the individual and combined effects of ultraviolet A (UV-A) and far-red (FR) light irradiation on the biomass, phytochemical accumulation, and antioxidant capacity of two lettuce cultivars in an artificial light plant factory. UV-A supplementation yielded a smaller leaf area and reduced biomass and nitrate content. In contrast, it improved the chlorophyll, soluble protein, soluble sugar, vitamin C, flavonoid, polyphenol, and anthocyanin contents and the 2,2-diphenyl-1-picrylhydrazyl radical-scavenging rate. FR irradiation resulted in a larger leaf area, whereas the lettuce biomass remained unchanged. Irradiation with both UV-A and FR light exhibited the most remarkable effect on leaf expansion and biomass, but reduced the phytochemical contents. A significant interaction between the cultivar and supplemented light was observed for most plant parameters.